Measurement and temporal and spatial characteristics of agricultural eco-efficiency under climate change: a case study of Anhui, China - Dong, Hao; Han, Jichang; Zhang, Yang; Chen, Tianqing; Sun, Zenghui; Hou, Xiandong; Liu, Yu (Frontiers in Sustainable Food Systems, 2023)
Agricultural eco-efficiency is an important index to evaluate the agricultural sustainable development and ecological economics, while simultaneously providing a metric for improvements to the rural environment and the stability of agricultural ecosystems. This study took Anhui province as a case, and applied unit survey and list analysis methodologies to quantify rural agricultural non-point source pollution (NPS). Input-oriented super-efficient DEA-SBM was used to measure agricultural ecoefficiency in the typical North-South Transition Zone, and evaluated spatial correlations and differences. This study showed that NPS was relatively stable, with less than 5% local variation in Chemical Oxygen Demand (COD), Total Nitrogen (TN), and Total Phosphorus (TP) pollutants. The environmental pressure caused by livestock breeding and the use of chemical fertilizers was very substantial, and the differences of rural agricultural NPS in Anhui Province had obvious north-south characteristics. The agricultural eco-efficiency exhibited an "inverted N" trend. Affected by the "Spatial proximity effect" and the "Matthew effect", it presented spatial agglomeration and positive spatial correlation. The regional differences were significant, and the heterogeneity increased in our study areas. The southern region had the greatest variation, followed by the northern region, with the smallest variation in the central region, although inter-regional differences were consistent. Though the rational allocation of resources, coordination between agricultural economic and environmental protection would be realized, and better conditions for the sustainable development of agricultural ecology and the long-term stability of agricultural ecosystem would be created.